2014
DOI: 10.1056/nejmoa1316222
|View full text |Cite
|
Sign up to set email alerts
|

A 52-Week Placebo-Controlled Trial of Evolocumab in Hyperlipidemia

Abstract: At 52 weeks, evolocumab added to diet alone, to low-dose atorvastatin, or to high-dose atorvastatin with or without ezetimibe significantly reduced LDL cholesterol levels in patients with a range of cardiovascular risks. (Funded by Amgen; DESCARTES ClinicalTrials.gov number, NCT01516879.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
438
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 630 publications
(486 citation statements)
references
References 15 publications
22
438
1
8
Order By: Relevance
“…Safety and tolerability profiles in the present study were consistent with previous studies of evolocumab6, 7, 8, 9, 10 and did not identify any risks. No anti‐evolocumab antibodies were detected in any participant.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Safety and tolerability profiles in the present study were consistent with previous studies of evolocumab6, 7, 8, 9, 10 and did not identify any risks. No anti‐evolocumab antibodies were detected in any participant.…”
Section: Discussionsupporting
confidence: 91%
“…The timing and magnitude of LDL‐C lowering after a dose of evolocumab were consistent with those seen in other studies in patients and healthy volunteers 5, 6, 8, 17, 31. For example, the randomized, double‐blind, placebo‐controlled, phase 2 MENDEL study showed that monotherapy with evolocumab 140 mg Q2W in 45 patients with hypercholesterolemia (baseline LDL‐C 3.6 mmol/L) reduced LDL‐C from baseline by 51% (95% CI –56% to –46%) after 12 weeks of treatment 31.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A total of 138 study arms from 35 studies were analyzed, comprising 45 539 patients (Table S1). 5, 11, 12, 13, 14, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43 Alirocumab was used in 18 studies (28 treatment arms), and evolocumab was used in 17 studies (39 treatment arms; Figure 1); placebo was the most common control used (52 control arms), with ezetimibe used in 17 arms, and standard therapy in 2 arms. Eight studies were of an exclusively FH population, and 5 studies included only patients intolerant to statins.…”
Section: Resultsmentioning
confidence: 99%
“…Alirocumab and evolocumab, either alone or in combination with statins and/or other lipid‐lowering therapies, have been shown in their respective phase 3 clinical trial programs (ODYSSEY and PROFICIO [Program to Reduce LDL‐C and Cardiovascular Outcomes Following Inhibition of PCSK9 In Different Populations]) to significantly reduce LDL‐C levels by up to 60% from baseline (depending on dosing regimen; Table) in patients with hypercholesterolemia, including those with familial hypercholesterolemia, moderate to very high cardiovascular risk, and statin intolerance 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62. The inclusion/exclusion criteria and other details of each phase 3 ODYSSEY and PROFICIO trial are shown in Table S2.…”
Section: Pcsk9 Inhibitors and Their Effects In Patients With Diabetesmentioning
confidence: 99%